HUBUNGAN POLA KONSUMSI PURIN DAN STATUS GIZI DENGAN KADAR ASAM URAT PADA MASYARAKAT DESA DI DUSUN MUNDUK TENGAH KABUPATEN BULELENG - Putu Ratna Dewi; Pande Putu Sri Sugiani; Lely Cintari (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2021)
Hyperuricemia is the case of elevated levels of serum uric acid above normal. Although Hyperuricemia is a disease that is not deadly, if not controlled properly can lead to various complications of other diseases such as Diabetes Mellitus and hypertension that have high mortality. Data from Riskesdas (2013) showed the prevalence of joint diseases in Bali at 19.3%. This research aims to determine the relationship of Purin consumption patterns and nutritional status with uric acid levels in rural communities in central Munduk Tengah, Buleleng Regency. The type of observational research with cross-sectional design with a population of 73 people and a sample of 63 people. The Data of Purin consumption patterns was collected by recapitating of SQ-FFQ forms. Nutritional status Data is determined by referring to the body mass index (BMI) by conducting height measurement and weighing weight. Data of uric acid levels in the blood is obtained by using multi-check tool parameters. Data that has been collected is then processed using computer software to determine whether  there is a relationship between variables. Some more samples have a normal quantities of purine intake per day (50.8%). Most samples consume a type of foodstuffs that have low purine (80.9%).  Most samples often consume food sources of purin at a frequency (52.4%). Most samples have a normal nutritional status (57.1%). Some more samples have normal uric acid levels (60.3%). Based on the results of data analysis using Chi-Square statistical test it’s known that there is a significant relationship (p = 0,000) between of purine consumption patterns with uric acid levels. No relationship (P = 0,259) between nutritional status with uric acid levels. The conclusion of this research is there is a relationship between of purin consumption patterns with uric acid levels and no relationship between nutritional status with uric acid levels. Keywords :  Hiperuricemia, Purine Consumption, Nutritional Status, Uric Acid Levels